PENGEMBANGAN MEDIA PERMAINAN ENGKLEK BERBASIS MODERN DI TK SEJAHTERA II NAMORAMBE - 1Odelia Agustine Br Ginting Br Ginting; Juli Yanti Harahap (STKIP Subang, 2024)
This development aims to determine the feasibility of learning media, namely modern-based engklek media for early childhood learning activities. This research is a type of research and development or Research and Development (R&D) with the ADDIE development model consisting of five stages, namely. Analysis, related to the analysis of the work environment situation so that it can be found what products need to be developed. Design, is the activity of designing products that are in accordance with what is needed. Development, is the activity of making and testing products. Implementation, is the activity of using the product. And Evaluation, is the activity of assessing whether each step of the activity and product that has been made is in accordance with the specifications or not. The focus of this study is the development of modern-based engklek media. The instrument used to collect data is a questionnaire given to the validator, namely the material expert validator, and the media expert validator. The results of the validation from the material expert carried out by the validator were obtained with an average total of 96% with the criteria